Mengenal Etika dalam Perspektif Filsafat Islam - Alkhadafi, Rahmad (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
The purpose of this paper is to recognize ethics in the perspective of Islamic philosophy. This research uses qualitative techniques based on a literature search. The research concludes that the formulation of ethics in Islam was done by various thinkers from various branches of knowledge, including theologians, mystics, and philosophers. The contributions of these multiple disciplines show how rich and complex the tradition of ethics in Islam is, with each branch of thought offering a unique perspective on developing a framework in Islamic ethics. The shortcoming of this study is that it discusses ethics in the perspective of Islamic philosophy in outline. In future research, this study suggests going deeper into the literature of Islamic ethics specifically on the thought of Muslim philosophers so that future studies of Islamic philosophy are not limited to topics such as the metaphysics of divinity, the creation of nature, and logic. Furthermore, by giving more attention to the study of ethics in Islam, the study of Islamic philosophy has the potential to open a space for dialogue with contemporary moral issues.